Fossils and Theories of Evolution in Gustave Flaubert’s Bouvard et Pécuchet - Anthony Zielonka (Flaubert: Revue Critique et Génétique)
This paper proposes a close textual analysis of Chapter III of the masterpiece of comic and satirical fiction that is Gustave Flaubert’s last novel, Bouvard et Pécuchet (1881). After exploring the sciences of medicine, cosmology, astronomy, and zoology, Flaubert’s “deux bonshommes” turn their attention to geology, paleontology, and even competeing theories of evolution. This chapter of the novel is of considerable interest as a comic tour-de-force in its ownright and when read in the context of the scientific discoveries, theories, controversies, and disputes (including conflicts between religious and scientific world views), that were raging in Flaubert’s lifetime. Interestingly, he chose to write about the latest scientific theories and discoveries in a decidedly skeptical and comic mode, as Bouvard and Pécuchet examine a wide range of theories concerning the evolution of the Earth and of humankind. As they discuss the ideas of Buffon, Cuvier, Lamarck, and Geoffroy Saint-Hilaire, aswell as of traditionalist Biblical scholars, Bouvard and Pécuchet, unsurprisingly, find their theories to be incompatible, contradictory and ultimately unconvincing. They draw their information from published scientific reports, books, and articles, but also from popular accounts published in magazines and newspapers. Flaubert very interestingly shows how distortions, inaccuracies, and simplifications in those accounts only serve further to confuse and depress the two seekers after scientific truth and, ultimately, to lead them to give up their pursuit of scientific knowledge altogether.